ETOS KERJA DALAM KAJIAN TEOLOGI ISLAM (ANALISIS PENELITIAN MAX WEBER TENTANG ETIKA PROTESTAN DI AMERIKA DAN ANALOGINYA DI ASIA) - Zulkarnain Zulkarnain (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
Max Weber's The Protestant Ethics and the Spirit of Capitalism explains the fact that in the context of modern Europe commercial leaders and capital owners, as well as those who are classified as high-skilled skilled workers, modern companies that are trained in the technical and commercial fields, most are Protestants. The author's purpose in raising this phenomenon is to compare Weber's research with theological views on work ethics. Methodologically, a comparative analysis approach was used in this study. The birth of the view that religion gave birth to an axiological-pragmatic value order that was able to change a society's condition from nothing to nothing, poor to rich, and so on, or in other words that the ethics of Protestant capitalism became a power that made Protestants more ethically superior working with Catholics or other religions is an inaccurate assessment. Theology and work ethic are very closely related because Work is a nature and is one of human identities, so work that is based on the principles of monotheistic faith, not only shows the nature of a Muslim, but at the same time elevates his dignity as a servant of Allah SWT. The findings in this study can be used by religious people in improving work ethic.Keywords: Work Ethic, Max Weber, Theology